2016
DOI: 10.1515/jpem-2015-0471
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of seven patients with hereditary tyrosinemia type 1

Abstract: This study showed once again that adherence to the treatment and a follow-up schedule of the patients are very important. Also it should not be forgotten that nodule formation can occur despite nitisinone treatment without an increase of AFP. Despite nitisinone treatment, HT1 patients still carry the risk of HCC. HCC must be detected before metastasis to other organs otherwise, patients may lose the chance for liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
16
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 24 publications
9
16
4
Order By: Relevance
“…In our study, the first signs were detected after six months of age (19/27) in contrast with report of Couce et al (21). Also growth retardation was detected at more high ratio (59.2%) in contrast with report of Gokay et al (19) and Zeybek et al (20). The mean interval from the first symptom of the diagnosis was 12.2 months.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In our study, the first signs were detected after six months of age (19/27) in contrast with report of Couce et al (21). Also growth retardation was detected at more high ratio (59.2%) in contrast with report of Gokay et al (19) and Zeybek et al (20). The mean interval from the first symptom of the diagnosis was 12.2 months.…”
Section: Discussioncontrasting
confidence: 98%
“…We have 29 HTI patients from 23 different families and consanguinity was noted in 14/23 (60.8%) of our patients' families. This is similar to the other studies of HTI reported from the Turkey (19,20). In Turkey HTI is not a part of national neonatal screening program, so diagnosis still depends on clinical suspicion and laboratory investigations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, these findings represent a solid group of patients suffering from a very rare disease that lacks proper guidelines and should at least raise questions about optimal management of these patients. Close monitoring of the patients under nitisinone treatment seems imperative since mortal consequences such as LF and HCC can occur even among patients under treatment with very high rates to be taken lightly . Measurement of SA levels in either blood or urine is suggested in the literature, and unmeasurable levels should be targeted for a successful treatment .…”
Section: Discussionmentioning
confidence: 99%